Geophysical Approach And Geochemistry Correlated To Discover Underground Water Flow Indicator To Mud Volcano In Quarter Volcanic System - Ridwan, Pandji; Fachrudin, Kurnia Arfiansyah; Ramadian, Aldrin; Wijayanti, Kemala (Faculty of Geological Engineering, Universitas Padjadjaran, 2021)
No less than 108 million meter3 of hot mud has been spread out from the earth since the burst first occurred in Porong, Sidoarjo at May 29th, 2006 until this day. This mud has covered the area for more than 717.027 ha with inundation that reaches many meters deep. If a close attention is being paid, 70% contain of the mud is water. Because of that, water volumes which have been produced is no less than 75 million m3. Therefore, information of subsurface geological data of the region around the burst site is needed to find out where the source of water came from. This study is meant to get a subsurface image of Porong so that a subsurface water channel that supplies water to the centre of mud burst can be found. Geophysical data, which is in the form of gravity method, Audio Magnetotelluric (AMT), and Magnetotelluric are correlated with geochemical study of elements of the mud. Pb, Zn, Mn, Ag, Cd, Sb, Au, Se, and Hg elements which the hot mud have is indication of hydrothermal influence at 100°C that come from the quarter volcanic system around the mud source such as Pananggungan Mountain and Arjuna Mountain. Not only that, result of measurement, gravity interpretation in form of Bouger anomaly, AMT, and MT data show three lineament structures in NE – SW direction in Porong, Sidoarjo. One of them extends from Watukosek Village in Pananggungan Mountain to the mud lake of Sidoarjo. This lineament is interpreted as a fault zone with 0.2 – 0.7 km deep in Watukosek Village and even gets deeper in the mud lake area (1.5 – 3 km deep). The Fault is a permeable zone which acts as the subsurface water channel. This channel is interpreted as the way of water flow, so the mud burst still continuous until this day.